2020
DOI: 10.1016/j.lungcan.2019.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of the focal adhesion kinase inhibitor defactinib (VS-6063) in previously treated advanced KRAS mutant non-small cell lung cancer

Abstract: Objectives: KRAS mutations, which occur in approximately 25% of lung adenocarcinoma cases, represent a major unmet clinical need in thoracic oncology. Preclinical studies have demonstrated that KRAS mutant NSCLC cell lines and xenografts with additional alterations in either TP53 or CDKN2A (INK4A/ARF) loci are sensitive to focal adhesion kinase (FAK) inhibition. Defactinib (VS-6063) is a selective oral inhibitor of FAK. Materials and Methods:Patients with previously treated advanced KRAS mutant NSCLC were pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 36 publications
0
79
0
Order By: Relevance
“…4 vs. 2.3; p = NS KRAS mut pts. 10.5 vs. 21.8; p = NS RO5126766 Chenard-Poirier et al [ 132 ] 2017 Phase I, OL, SC MEK/RAF 10 mut Response NA NA Selumetinib Jänne et al [ 133 ] 2017 Phase III, R, DB, MC MEK 510 mut PFS 3.9 vs. 2.8; p = NS 8.7 vs. 7.9; p = NS Defactinib Gerber et al [ 134 ] 2019 Phase II, OL, SC FAK 55 mut PFS at 12 wks 45 days NA DB , double blind; DCR , disease control rate; DPE , disease progression event count; FAK , focal adhesion kinase; KRAS , Kirsten rat sarcoma viral oncogene homolog; MC , multicenter; MEK , MAPK/ERK kinase; mTOR , mammalian target of rapamycin; mut , mutant; NS , non-significant; NA , not announced; OL , open label; OS , overall survival; PFS , progression-free survival; pt , patient; R , randomized; RAF , rapidly accelerated fibrosarcoma; RAS , rat sarcoma virus; SC , single-center; wks , weeks; wt , wild type *Patients with non-small cell lung cancer #In months unless otherwise stated …”
Section: Kras As a Therapeutic Target In Nsclcmentioning
confidence: 99%
“…4 vs. 2.3; p = NS KRAS mut pts. 10.5 vs. 21.8; p = NS RO5126766 Chenard-Poirier et al [ 132 ] 2017 Phase I, OL, SC MEK/RAF 10 mut Response NA NA Selumetinib Jänne et al [ 133 ] 2017 Phase III, R, DB, MC MEK 510 mut PFS 3.9 vs. 2.8; p = NS 8.7 vs. 7.9; p = NS Defactinib Gerber et al [ 134 ] 2019 Phase II, OL, SC FAK 55 mut PFS at 12 wks 45 days NA DB , double blind; DCR , disease control rate; DPE , disease progression event count; FAK , focal adhesion kinase; KRAS , Kirsten rat sarcoma viral oncogene homolog; MC , multicenter; MEK , MAPK/ERK kinase; mTOR , mammalian target of rapamycin; mut , mutant; NS , non-significant; NA , not announced; OL , open label; OS , overall survival; PFS , progression-free survival; pt , patient; R , randomized; RAF , rapidly accelerated fibrosarcoma; RAS , rat sarcoma virus; SC , single-center; wks , weeks; wt , wild type *Patients with non-small cell lung cancer #In months unless otherwise stated …”
Section: Kras As a Therapeutic Target In Nsclcmentioning
confidence: 99%
“…Studies revealed that defactinib inhibited FAK phosphorylation at Y397 and a combination of defactinib with paclitaxel showed decreased cell proliferation and apoptosis in ovarian cancer cells (Kang et al, 2013). In phase 2 trials, defactinib has moderate activity in KRAS mutant non-small cell lung carcinoma but failed to boost the clinical trial outcomes as a maintenance therapy (Gerber et al 2020). Verastem screened a combination of defactinib and paclitaxel in women with ovarian cancer in a phase I/Ib clinical trial (#NCT01778803).…”
Section: Pnd-1186 (Vs-4718)mentioning
confidence: 99%
“…Our initial analysis showed that tumor cell viability decreased by approximately 40%, when treated with ≤5.0 μM, VS-6063, a chemical inhibitor of active FAK which blocks its Y 397 autophosphorylation ( Supplementary Figure S2A ). Given the limitation of clinical efficacy of this FAK inhibitor against epithelia-origin human cancers ( Jones et al, 2015 ; Xu et al, 2017 ; Gerber et al, 2020 ), we examined the combinatorial inhibition strategy for this inhibitor-based targeting by performing cell viability-based chemical inhibitor screening. As shown in Supplementary Figure S2 , two out of more than 30 anti-tumor chemical agents screened, the pharmacological agents of epigenetic drivers BRD4 (JQ1) and histone deacetylase (HDAC, LBH589) ( Filippakopoulos et al, 2010 ), and the pro-survival Akt (MK-2206) and Bcl-2 (ABT-737), exhibited strong cooperative effects with VS-6063 in terms of cell viability inhibition.…”
Section: Resultsmentioning
confidence: 99%